Spatial and temporal variations of persistent organic pollutants impacted by episodic sediment resuspension in southern Lake Michigan - Miller, Sondra M (Journal of Great Lakes research, 2010)
The impacts of large-scale, episodic sediment resuspension on the cycling of polychlorinated biphenyl congeners (PCBs) were examined using a spatially coordinated air and water sampling strategy conducted in southern Lake Michigan in the late winters of 1998, 1999, and 2000. We found no significant temporal changes in gas phase, dissolved phase, or suspended sediment PCB concentrations despite large-scale seasonal storms occurring before and after sampling campaigns. Only gas phase and suspended sediment PCBs varied spatially. Higher total suspended material (TSM) concentrations and fraction organic carbon (foc ) were measured at sampling stations located in the near-shore region of southern Lake Michigan than at open-water sampling stations. Gas phase concentrations (ΣPCBg) were higher in the west (0.436 ± 0.200 ng/m3, n = 11) and south (0.408 ± 0.286 ng/m3, n = 5) than the east (0.214 ± 0.082 ng/m3, n = 10) and central (0.253 ± 0.145 ng/m3, n = 8) regions of southern Lake Michigan. Dissolved phase concentrations (ΣPCBd) averaged 0.18 ± 0.024 ng/L (n = 52); suspended sediment concentrations (ΣPCBs) accounted for between 4% and 72% (23 ± 4%, n = 52) of the total ΣPCB concentrations (ΣPCBT = ΣPCBd + ΣPCBs). Despite no consistent temporal variations in both dissolved phase or suspended sediment ΣPCB concentrations, there were temporal and spatial variations in the distribution shift between phases that can be linked to sediment resuspension, not a state of equilibrium. Specifically, our analysis suggests sediment resuspension results in preferential sorption of heavier, more chlorinated PCB congeners